Look before washing and cleaning: A caveat to pathologists and anthropologists. (April 2021) - Mazzarelli, Debora; Tambuzzi, Stefano; Maderna, Emanuela; Caccia, Giulia; Poppa, Pasquale; Merelli, Vera; Terzi, Marco; Rizzi, Agostino; Trombino, Luca; Andreola, Salvatore; Cattaneo, Cristina
Abstract: Partially or totally skeletonized bodies are undoubtedly the most challenging scenario to deal with for forensic pathologists and anthropologists. Indeed, in such cases, being able to figure out the cause and manner of death is often tricky. Human remains require to be washed and cleaned before a thorough assessment of any signs of trauma. However, bones and any fragment of more or less putrefied soft tissues may be home to crucial traces for investigative purposes. They are often located in the context of apparently meaningless dirt and, sometimes they are even invisible to the naked eye. Therefore, their careless cleaning inevitably leads to an unintentional loss of such traces with a negative impact on subsequent investigations. For these reasons before proceeding with cleaning, exhaustive examination and sampling must be carried out. In particular fragments of soft tissues, even if putrefied, are absolutely not to be considered as a hindrance for forensic purposes, since they could still provide valuable information after histological examination. Finally, forward-thinking professionals should think about the possible presence of exogenous micro-traces of forensic concern and collect specimens to be analyzed through in-depth analyses, such as Scanning Electron Microscopy with Energy Dispersive X-ray Spectrometry (SEM/EDX). The present series of cases demonstrates that crucial forensic information can be obtained through the analysis of apparently meaningless residues and even of micro-traces not visible to the naked eye and mixed with trivial dirt. Highlights: In forensic field dirt may be a key factor. Always pay attention before washing and cleaning human remains. Fragments of putrefied soft tissues near skeletal traumatized areas should always be assessed. Glycophorin A is useful in assessing hemorrhagic infiltration in putrefied tissues. SEM/EDX may help in identifying the place of death and the murder weapon.